1980
DOI: 10.1161/01.res.47.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium on the sarcomere length-tension relation in rat cardiac muscle. Implications for the Frank-Starling mechanism.

Abstract: The objective of these experiments was to better understand the factors responsible for the decline in tension at short sarcomere lengths in cardiac muscle. We measured the effects of variation of extracellular calcium concentration on the sarcomere length-tension relation in thin trabeculae and papillary muscles excised from right ventricles of rats. Sarcomere lengths were measured by optical diffraction. Experiments were carried out using two protocols. In the primary protocol, the muscle was allowed to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The role of changing contraction duration, induced deactivation, and increased activation in the immediate enhancement of myocardial performance due to lengthening have recently been discussed (Jewell, 1977;Gordon and Pollack, 1980), and it is not clear that the present experiments shed further light on this subject.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The role of changing contraction duration, induced deactivation, and increased activation in the immediate enhancement of myocardial performance due to lengthening have recently been discussed (Jewell, 1977;Gordon and Pollack, 1980), and it is not clear that the present experiments shed further light on this subject.…”
Section: Discussionmentioning
confidence: 85%
“…Activation factors which most likely depend on muscle length have been recently considered (Jewell, 1977;Gordon and Pollack, 1980) as including: (1) changing of contraction duration, (2) decreased deactivation, and (3) increased activation. As the slow increase of pressure occurred at a constant ventricular volume, the most straightforward conclusion is that slow changes take place when muscle fibers are at near-constant length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular basis of this intrinsic system is not known. It has been speculated to reflect better alignment of the myofibrillar arrays (Sonnenblick et al 1973) or regulation of intracellular calcium (Ca 2+ ) (Gordon and Pollack 1980;Van Henningen et al 1982;Gillebert et al 1989). Even the embryonic heart manifests a Frank-Starling response well before innervation (Benson et al 1989).…”
mentioning
confidence: 99%
“…GORDON and POLLACK [19] measured the effect of calcium on the sarcomere length-tension curve in thin trabeculae from rat right ventricle and confirmed that the height of the curve was progressively depressed as extracellular calcium levels were reduced from 2.5 to 0.3 mM (similarly to curves 5 to 3 in Fig. 3).…”
Section: Force-velocity Relation Of Tetanized Cardiac Musclementioning
confidence: 67%